Edukasi Pengelolaan Lingkungan Permukiman pada Daerah Terdampak Abrasi Desa Bajoe - La Hamimu; Bahdad Bahdad; Laode Ihksan Juarzan; Fitriani Fitriani; La Ode Andimbara; Alfirman Alfirman (Jurnal Ilmiah Pangabdhi, 2021)
Bajoe Village is one of the coastal areas in Province of Southeast Sulawesi has experienced abrasion within a period of 10 years. So it is necessary to provide education on the management of the residential environment that will be affected by abrasion. The method used is the analysis of satellite images using google aerth and SAS Planet, and the lecture method. The result of this activity is that in Tiga Hamlet, it was detected that coastal abrasion had occurred, so that mangrove planting was carried out in Tiga Hamlet. Education is carried out for students so that they can clearly see the change in the environment due to abrasion in Bajoe Village.Then have a discussion with the village head as a stakeholder about the results obtained so that it expected to provide consideration in making decisions on the development of Bajoe Village.